Development of Community Satisfaction Instrument Measurement in Public Health Center Based on Android - Zogara, Aprianus Umbu; Woro Kasmini Handayani, Oktia; Sunawan, Sunawan (Journal of Research and Educational Research Evaluation, 2018)
The quality of health services can be measured by measuring the indices of public satisfaction on services provided at a public health center. Measurements are certainly done by using instruments to facilitate the collection of data. The purpose of this research is to develop the measurement instrument of community satisfaction index at public health center based on android. The benefistsof the research that can be used as a standard guide in measuring public satisfaction. The instruments currently used do not measure the index of community satisfaction as expected based on indicators of community satisfaction. This research is a development research conducted on unit of outpatient service Ngemplak Simongan Public Health Center, Semarang City in April-May 2018. The sampling technique using accidental sampling Test method of content validity using expert judgment, construct validity using Exploratory Factor Analysis (EFA), while reliability testing using Cronbach Alpha. The develop instrument consists of five dimensions of measurement which includes tangible, responsivenees, reliability, assurance and emphaty. The result ofthe research shows that all statement items of 72 items from all service units are valid by content based on expert’s judgment calculated using Aiken V formula and as many 72 item of valid statement construct from all service units, as well as instruments of all service units stated to have high and very high reliability coefficients so it is feasible to use.